The Influence of Investment, Debt, and Dividend Policies on the Stock Return of Shariah Compliant Companies in Indonesia (ISSI) - Razali Haron; Mukhtar Arif Siraj (Global Review of Islamic Economics and Business, 2021)
This study aims to analyze the impact of investment, debt, and dividend policies on the stock return of the companies listed in the Indonesia Sharia Stock Index (ISSI) from 2016 up to 2020. The sample stocks used in this study covers all the shariah compliant companies that were consistently listed during the study period, involving 158 companies with 790 observations. The proxies of stock return are annualized stock return, Sharpe ratio, and Treynor ratio. Investment policy is represented by price earnings ratio (PER), debt policy by debt to asset ratio (DAR), and dividend policy by dividend yield (DY). The generalized method of moment (GMM) is a regression technique that is employed in this study. The regression model should pass the AR(2) and Hansen tests to avoid autocorrelation and validity issues. This study provides important evidence that investment policy positively affects stock return (annualized stock return and Treynor ratio). In contrast, investment policy negatively affects the Sharpe ratio. Furthermore, there is a significant negative relationship between debt policy and the Sharpe ratio. Lastly, dividend policy is reported to significantly influence stock return, positive with Treynor ratio, while negative with stock return (annualized). The study relates its findings to the relevant theories involving the trade-off, signalling, and the bird in the hand theories.